Fatigue and fretting of mixed metal self-piercing riveted joint. (February 2016) - Huang, Li; Bonnen, John; Lasecki, John; Guo, Haiding; Su, Xuming
Highlights: SPR joints with dissimilar metal sheets between AA6111-T4 and HSLA340 were investigated. Fatigue crack initiation life of SPR was found to be much shorter than its crack growth life. Fretting was shown to be critical to the crack initiation of SPR. Abstract: The fatigue behavior of self-piercing rivet (SPR) joints joining differing thicknesses of AA6111-T4 aluminum and HSLA340 steel sheets in lap shear geometry was investigated in this paper. Crack initiation in the aluminum sheet was the dominant failure mode, while unexpected rivet shank failure tended to occur at high loading levels. Fretting wear was also observed at interface between aluminum and steel sheets as well as between the rivet and sheets under sinusoidal cyclic tension–tension loading. An Energy Dispersive X-ray (EDX) analysis of fretting debris revealed the presence of oxides of aluminum and zinc. Fretting was shown to be critical to crack initiation. For initiations in the aluminum sheet, micro cracks were found to nucleate early in the fatigue life, and crack initiation life was found to be much shorter than crack growth life.